2001
DOI: 10.1385/abab:90:2:107
|View full text |Cite
|
Sign up to set email alerts
|

One- and Two-Stage Upflow Anaerobic Sludge-Bed Reactor Pretreatment of Winery Wastewater at 4–10°C

Abstract: The operating performance of a single and two (in series) laboratory upflow anaerobic sludge-bed (UASB) reactors (2.7-L working volume, recycle ratio varied from 1:1 to 1:18) treating diluted wine vinasse was investigated under psychrophilic conditions (4-10 degreesC). For a single UASB reactor seeded with granular sludge, the average organic loading rates (OLRs) applied were 4.7, 3.7, and 1.7 g of chemical oxygen demand (COD)/(L.d) (hydraulic retention times [HRTs] were about 1 d) at 9-11, 6 to 7, and 4 to 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 5 publications
0
17
0
6
Order By: Relevance
“…The homoacetogenic bacteria seems less likely to exist in the reactor environment because the hydrogen concentration was much lower than can be reached by homoacetogenic bacteria (about 300 nM), which was also raised elsewhere (Xu et al, 2010). Previous studies of EGSB or UASB reactors revealed serious formation of acidifying sludge layer around the granules under psychrophilic conditions (Kalyuzhnyi et al, 2001). It was reported that under psychrophilic conditions, acidifiers have a high yield of 0.22 gCOD VSS g À1 COD removed (van Lier et al, 1997) owing to low starvation rate of acidifiers at low temperature.…”
Section: Pathway Of Influent Organic Carbonmentioning
confidence: 96%
“…The homoacetogenic bacteria seems less likely to exist in the reactor environment because the hydrogen concentration was much lower than can be reached by homoacetogenic bacteria (about 300 nM), which was also raised elsewhere (Xu et al, 2010). Previous studies of EGSB or UASB reactors revealed serious formation of acidifying sludge layer around the granules under psychrophilic conditions (Kalyuzhnyi et al, 2001). It was reported that under psychrophilic conditions, acidifiers have a high yield of 0.22 gCOD VSS g À1 COD removed (van Lier et al, 1997) owing to low starvation rate of acidifiers at low temperature.…”
Section: Pathway Of Influent Organic Carbonmentioning
confidence: 96%
“…In situ determinations of kinetic sludge characteristics (apparent Vm and Km) revealed the existence of substantial mass transfer limitations for the soluble substrates inside the reactor sludge bed. Therefore, application of higher recycle ratios is essential for enhancement of UASB pretreatment under psychrophilic conditions [55]. The conventional UASB reactors concept showed severe limitations mainly owing to problems related to mass transfer resistance or the appearance of concentration gradients inside the systems [56].…”
Section: Upflow Anaerobic Sludge Blanket (Uasb) Reactorsmentioning
confidence: 99%
“…The feed was made alkaline with the addition of NaOH (0.5-1.0 ml 10 N NaOH/l feed), and was supplemented with nutrients corresponding to a COD/N/P ratio of 400/7/1 [9]. Due to the low nutrient content present in winery wastewater, the addition of nitrogen and phosphate sources is recommended for cellular growth in the biological treatment process [14,16,31] to maintain a minimum COD:Tot N:P ratio of 400:7:1. The main characteristics of the feed are given in Table 2.…”
Section: Feed Characteristics and Reactor Inoculummentioning
confidence: 99%